Trade-offs between photosynthetic capacity and structural economy underlie the rapid proliferation of floating Ulva prolifera - Ruili Niu; Cancan Xia; Min Cha; Cui Han; Bojian Zhong; Xiaojie Liu (Harmful Algae, 2026)

Identification of colorectal cancer molecular subtypes and prognostic features based on basement membrane-related genes - Leilei Yang; Zhiqing Ji; Yufeng Ren; Chengfeng Fang; Jiaju Han; Dinghai Luo; Ruili Zhang; Shenkang Zhou (Journal of Applied Genetics, 2026)

Exploring mesenchymal stem cell niches for regeneration - Han Zhang; Duo Liu; Tong Wu; Chider Chen; Jiuhui Jiang; Ruili Yang (Science Bulletin, 2025)

Numerical study of regular wave dynamics for optimizing coral reef restoration - Jiuming Han; Yanjun Li; Xizeng Zhao; Tao Liu; Yanzhen Gu; Shuangyan He; Peiliang Li; Ruili Sun (Ocean Engineering, 2025)

The transcriptional changes of LrgA discriminates the responsiveness of Staphylococcus aureus towards blue light from that of photodynamic inactivation - Ruili Yang; Yi Xu; Jinchun Xu; Yali Li; Xiaoxiao Wan; Rui Kong; Chao Ding; Han Tao; Hui-Li Wang (Journal of Photochemistry and Photobiology B: Biology, 2024)

Heat-shock transcription factor HsfA8a regulates heat stress response in Sorbus pohuashanensis - Yuyan Li; Qianwen Wu; Lingyi Zhu; Ruili Zhang; Boqiang Tong; Yan Wang; Yi Han; Yizeng Lu; Dequan Dou; Zhihui Tian; Jian Zheng; Yan Zhang (Planta, 2024)

An ultra-sensitive photoelectrochemical sensor for chlorpyrifos detection based on a novel BiOI/TiO2 n-n heterojunction - Ruili Lyu; Yiting Lei; Chi Zhang; Gaiping Li; Runping Han; Lina Zou (Analytica Chimica Acta, 2023)

Semi-Analytical Solution of Transverse Vibration of Cylinders with Non-Circular Cross-Section Partially Submerged in Water - Huixuan Han; Yishuo Guo; Ruili Huo (Journal of Marine Science and Engineering, 2023)
The free transverse vibration of a surface-piercing, vertical cylinder partially submerged in water was studied. The cylinder had an arbitrary non-circular, but symmetric, cross-section in the vibration direction. The water was assumed to be an incompressible and inviscid fluid. The effect of the surface waves of water was neglected in the analysis. The exact solution of velocity potential of water was derived by the method of separation of variables. The unknown coefficients in the solution of the velocity potential were expressed in the form of integral equations, including the dynamic deformation of the beam. Then, the governing differential equation of bending vibration of the cylinder under the hydrodynamic pressure was obtained. The Galerkin method was used to obtain the eigenvalue equation by expanding the wet modes of the cylinder into a series of dry modes. The elliptical cylinders partially submerged in water were taken as the numerical example. The accuracy of the proposed method was evaluated by the convergence studies. As a consequent result, the non-dimensional added virtual mass incremental (NAVMI) factor solutions were compared to the present Galerkin solutions, which can be used as a benchmark test for more sophisticated numerical simulations of computational fluid dynamics.

Identification and genetic analysis of major gene ST3GAL4 related to serum alkaline phosphatase in chicken - Hehe Tang; Yanchao Ma; Jianzeng Li; Zhenzhen Zhang; Wenting Li; Chunxia Cai; Lujie Zhang; Zhuanjian Li; Yadong Tian; Yanhua Zhang; Jinqing Ji; Lu Han; et al. (Research in Veterinary Science, 2023)

Dl-3-n-Butylphthalide improves lipopolysaccharide-induced depressive-like behavior in rats: involvement of Nrf2 and NF-κB pathways - Mengqi Yang; Ruili Dang; Pengfei Xu; Yujin Guo; Wenxiu Han; Dehua Liao; Pei Jiang (Psychopharmacology, 2018)

Identification and association of novel lncRNA pouMU1 gene mutations with chicken performance traits - Tuanhui Ren; Yanting Zhou; Yu Zhou; Weihua Tian; Zhenzhen Gu; Song Zhao; Yadi Chen; Ruili Han; Xiaojun Liu; Xiangtao Kang; Zhuanjian Li (Journal of Genetics, 2017)

Association study of a common genetic variant in pre-miR-1596 with chicken performance traits - Hong Li; Yadong Tian; Guirong Sun; Xiaojun Liu; Ruirui Jiang; Ruili Han; Guoxi Li; Xiangtao Kang (Molecular Biology Reports, 2014)

Cloning of TPO gene and associations of polymorphisms with chicken growth and carcass traits - Xinyan Hou; Ruili Han; Yadong Tian; Wanying Xie; Guirong Sun; Guoxi Li; Ruirui Jiang; Xiangtao Kang (Molecular Biology Reports, 2013)

Polymorphisms of the pro-opiomelanocortin and agouti-related protein genes and their association with chicken production traits - Yichun Bai; Guirong Sun; Xiangtao Kang; Ruili Han; Yadong Tian; Hong Li; Yang Wei; Shikang Zhu (Molecular Biology Reports, 2012)

Novel SNPs in the PRDM16 gene and their associations with performance traits in chickens - Ruili Han; Yang Wei; Xiangtao Kang; Hong Chen; Guirong Sun; Guoxi Li; Yichun Bai; Yadong Tian; Yanqun Huang (Molecular Biology Reports, 2012)